Digital Innovation in Islamic Religious Education: A Study of Madrasah Aliyah in Banda Aceh - Rijal, Fakhrul; Hasanuddin, Hasanuddin; Mardhiah, Ainal (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
The digital era has reshaped educational paradigms, requiring innovative approaches across disciplines, including Islamic Religious Education (PAI) at the Madrasah Aliyah level. This study explores the forms and effectiveness of digital innovations implemented in PAI instruction at selected Madrasah Aliyah in Banda Aceh. Using a descriptive qualitative method, data were collected through classroom observations, in-depth interviews, and document analysis at two public madrasahs. The findings reveal several forms of digital innovation: (1) the use of instructional videos and religious animations; (2) gamified formative assessments via platforms such as Kahoot! and Quizizz; (3) the use of Learning Management Systems like Google Classroom; and (4) limited development of culturally grounded digital content rooted in Acehnese traditions. While these innovations have positively influenced student engagement, comprehension, and digital literacy, implementation remains uneven due to infrastructural limitations, gaps in teacher competence, and insufficient institutional support. The study emphasizes the potential of contextually responsive digital tools to enhance Islamic learning when accompanied by sustained capacity building and systemic support. By highlighting both pedagogical benefits and practical constraints, this research contributes to the discourse on culturally informed, technology-integrated Islamic education.